2010
DOI: 10.1007/s10236-010-0348-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale modeling of Puget Sound using an unstructured-grid coastal ocean model: from tide flats to estuaries and coastal waters

Abstract: Water circulation in Puget Sound, a large complex estuary system in the Pacific Northwest coastal ocean of the United States, is governed by multiple spatially and temporally varying forcings from tides, atmosphere (wind, heating/cooling, precipitation/evaporation, pressure), and river inflows. In addition, the hydrodynamic response is affected strongly by geomorphic features, such as fjord-like bathymetry and complex shoreline features, resulting in many distinguishing characteristics in its main and sub-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The model employs the Smagorinsky scheme for horizontal mixing [35] and the Mellor Yamada, level 2.5, turbulent closure scheme for vertical mixing [36]. FVCOM has been widely used to simulate circulations in coastal and estuarine environments [29,[37][38][39][40][41][42], storm surge predictions [43][44][45], and nearshore restorations [15,16].…”
Section: Coastal Ocean Hydrodynamic Model-fvcommentioning
confidence: 99%
“…The model employs the Smagorinsky scheme for horizontal mixing [35] and the Mellor Yamada, level 2.5, turbulent closure scheme for vertical mixing [36]. FVCOM has been widely used to simulate circulations in coastal and estuarine environments [29,[37][38][39][40][41][42], storm surge predictions [43][44][45], and nearshore restorations [15,16].…”
Section: Coastal Ocean Hydrodynamic Model-fvcommentioning
confidence: 99%
“…The water quality computations were conducted offline using a previously computed hydrodynamic solution over the same model grid. The hydrodynamic model of Puget Sound at two separate grid resolutions has been discussed in detail previously Yang and Khangaonkar 2010) and is presented here in a summary form. In this paper, we focus on the aspects of model setup related to estimates of loads to the system from various rivers, streams, and wastewater sources, and the biogeochemical configuration of the model.…”
Section: Model Description and Configurationmentioning
confidence: 99%
“…Using approximate circulation analysis and simplified formulation of phytoplankton kinetics, they demonstrated that phytoplankton growth in Puget Sound is closely coupled to the seasonal variation and circulation characteristics. Subsequent Puget Sound-wide model development efforts have ranged from simplified box models (Friebertshauser and Duxbury 1972;Hamilton et al 1985;Li et al 1999;Cokelet et al 1990; Babson et al 2006) to vertical 2-D models (Lavelle et al 1991) to fully 3-D baroclinic numerical models Sutherland et al 2011;Yang and Khangaonkar 2010;Nairn and Kawase 2002). However, these studies have focused on hydrodynamics and physical processes only.…”
mentioning
confidence: 99%
“…FVCOM uses unstructured triangular cells in the horizontal plane and a sigma-stretched coordinate system in the vertical direction to better represent the complex horizontal geometry and bottom topography of an estuary. FVCOM has been applied to simulate tidal dynamics and circulations in many estuarine and coastal waters (Zheng et al 2003;Zhao et al 2006;Weisberg and Zheng 2006;Hu et al 2008;Huang et al 2008;Chen et al 2009;Yang and Khangaonkar 2010;Lai et al 2010;Yang et al 2011;Xing et al 2011). …”
Section: Numerical Modelmentioning
confidence: 99%